2000
DOI: 10.1086/317053
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Conditions of the X‐Ray Emission Line Regions in the Circinus Galaxy

Abstract: We present a detailed X-ray spectral analysis of the Circinus galaxy using archival data obtained with the ASCA satellite. The spectrum shows numerous emission lines in the soft X-ray band from highly ionized ions, as well as Compton reÑection and Ñuorescent lines from neutral or near-neutral matter. We analyze the spectrum in the context of a self-consistent recombination cascade model and Ðnd that a nearly Ñat di †erential emission measure (DEM) distribution in ionization parameter Ðts the data. For a Ðxed s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 30 publications
6
30
1
Order By: Relevance
“…However, the temperature of the hotter MEKAL component is very high keV, which is the hottest (kT h \ 80 temperature at which the model is tabulated) and unconstrained, making it impossible to distinguish the M2]M2 from the M2]P model. The temperature of the cooler MEKAL (kT D 0.6 keV) agrees well with the collisional ionization equilibrium model of Sako et al (2000). The addition of a second MEKAL component to either the M1]P or M2]P model does not signiÐcantly (at Z70% conÐdence) improve the Ðt.…”
Section: T He Northwest Regionsupporting
confidence: 70%
See 3 more Smart Citations
“…However, the temperature of the hotter MEKAL component is very high keV, which is the hottest (kT h \ 80 temperature at which the model is tabulated) and unconstrained, making it impossible to distinguish the M2]M2 from the M2]P model. The temperature of the cooler MEKAL (kT D 0.6 keV) agrees well with the collisional ionization equilibrium model of Sako et al (2000). The addition of a second MEKAL component to either the M1]P or M2]P model does not signiÐcantly (at Z70% conÐdence) improve the Ðt.…”
Section: T He Northwest Regionsupporting
confidence: 70%
“…A hard (! D 0) power-law continuum and strong Fe Ka emission were found in earlier ASCA (Matt et al 1996 ;Sako et al 2000) and BeppoSAX (Guainazzi et al 1999) observations, as well as in the Chandra HETGS observation (Sambruna et al 2001b). These properties are expected if we see the nuclear spectrum Compton reÑected from the far side of a putative dense torus and do not directly view the nucleus itself.…”
Section: Nuclear Spectrumsupporting
confidence: 65%
See 2 more Smart Citations
“…The line spectrum above ∼2 keV clearly originates from low ionized matter (Matt et al 1996;Netzer et al 1998;Sako et al 2000). It was shown that it is fully compatible with reflection from the inner surface of a mildly ionized torus, the same matter likely responsible for the absorption of the nuclear radiation: this interpretation leads to an estimate of the inner radius of the torus of ∼0.2 pc (Bianchi et al 2001).…”
Section: Introductionmentioning
confidence: 82%